Axial length and subfoveal choroidal thickness in individuals with age-related macular degeneration - Wang, Chih-Ping (Taiwan J Ophthalmol, 2015)
PURPOSE: To compare axial length (AL) and subfoveal choroidal thickness (SFCT) between individuals with age-related macular degeneration (AMD) and controls with no lesions. METHODS: This was a case-control study. In total, 853 eyes of 484 patients (>65 years), including 397 eyes at various AMD stages and 456 eyes with no fundus lesions (controls) were recruited. Using color fundus photography, eyes were grouped according to AMD degree. AL was automatically measured using IOL Master and SFCT was manually measured by two independent observers. The associations among age, AL, SFCT, and each AMD grade were analyzed. RESULTS: Out of 853 eyes, 456 had no lesions, 217 contained drusen only, 134 had early AMD, and 46 had late AMD. The eyes with late AMD were older (p = 0.007) and had longer AL (p ≥ 0.001) and thinner SFCT (p < 0.001) compared with groups of no fundus lesions, drusen only, and early AMD. SFCT in eyes with late AMD decreased by 19.20 μm (p = 0.049), 24.78 μm (p = 0.029), and 15.56 μm (p = 0.162) compared with groups of no fundus lesions, drusen only, and early AMD, respectively. SFCT decreased by 14.18 μm/mm increase in AL (p < 0.001). The odds ratio (OR) for late AMD by longer AL (≥25 mm) and thinner SFCT (<240 μm) was 4.54 (χ(2) = 9.36; p = 0.002) and 4.86 (χ(2) = 17.62; p < 0.001), respectively, and was 9.57 (χ(2) = 18.07; p < 0.001) when both AL ≥ 25 ≥m and SFCT < 240 μm. CONCLUSION: Eyes with late AMD have distinct reduced SFCT and elongated AL. Eyes with thinner SFCT and longer AL showed high ORs for late AMD and even higher ORs when both factors were simultaneously present. These findings illustrate the crucial pathophysiological role of these two important ocular fac tors and arouse our attention to patients with both characteristics, especially in Asian countries where the prevalence of myopia are disturbingly high.